Effects of Laser Radiation on Mitochondria and Mitochondrial Proteins Subjected to Nitric Oxide - Osipov, Anatoly N.; Machneva, Tatiana V.; Buravlev, Evgeny A.; Vladimirov, Yury A. (Frontiers in Medicine, 2018)
The biological roles of heme and nonheme nitrosyl complexes in physiological and pathophysiological conditions as metabolic key players are considered in this paper. Two main physiological functions of protein nitrosyl complexes are discussed – (1) a depot and potential source of free nitric oxide (NO) and (2) a controller of crucial metabolic processes. The first function is realized through the photolysis of nitrosyl complexes (of hemoglobin, cytochrome C or mitochondrial iron-sulfur proteins). This reaction produces free NO and subsequent events are due to the NO physiological functions. The second function is implemented by the possibility of NO to bind heme and nonheme proteins and produce corresponding nitrosyl complexes. Enzyme nitrosyl complex formation usually results in the inhibition (or enhancement in the case of guanylate cyclase) of its enzymatic activity. Photolysis of protein nitrosyl complexes, in this case, will restore the original enzymatic activity. Thus, cytochrome C acquires peroxidase activity in the presence of anionic phospholipids and this phenomenon can be assumed as a key step in the programmed cell death. Addition of NO induces the formation of cytochrome C nitrosyl complexes, inhibits its peroxidase activity and hinders apoptotic reactions. In this case, photolysis of cytochrome C nitrosyl complexes will reactivate cytochrome C peroxidase activity and speed up apoptosis. Control of mitochondrial respiration by NO by formation or photolytic decay of iron-sulfur protein nitrosyl complexes is an effective instrument to modulate mitochondrial metabolism. These questions are under discussion in the present paper.